The Evolving Concept of Poor-Prognosis for Women Undertaking IVF and the Notion of Growth Hormone as an Adjuvant; A Single-Center Viewpoint - Yovich, John L.; Ye, Yun; Regan, Sheena L. P.; Keane, Kevin Noel (Frontiers in Endocrinology, 2019)
IVF is currently regarded as a successful new technology with the number of IVF children currently well over 8 million worldwide. This has been achieved by an explosive plethora of facilities. However, from its earliest history, IVF has been beset by poor-prognosis on a treatment cycle basis, an aspect which has been a constant feature for the majority of treatments to this stage. Current ANZARD reporting shows that IVF clinics have live birth productivity rates (from combined initiated fresh and frozen cycles) ranging from 9.3% to 33.2%. Over the past 40 years there have been a number of innovations which have steadily moved the success rates forward, but progress is held back by an intransigent group of women who can be classified as being poor-prognosis from one or more adverse factors, namely advanced age (>40 years), poor ovarian response (POR) to ovarian stimulation, inability to generate high quality blastocyst-stage embryos, recurrent implantation failure or recurrent early pregnancy losses. A number of strategies are variously applied including the use of recombinant growth hormone (GH) adjuvant therapy. Our retrospective studies at PIVET over the past decade show a 6.2-fold chance of live birth for fresh cycle embryo transfers following GH injections of 1 to 1.5 IU daily given for 3 to 6 weeks in the lead-up to the trigger for ovum pick-up. We have also recently reported the live birth rates from frozen embryo transfers utilizing those blastocyst embryos generated under GH influence and showed the live birth rate was 2.7-fold higher in a carefully matched poor-prognosis group. This experience has been compared to the total 41 GH studies reported since the year 2000, the majority matching those of PIVET with significant increases in both oocyte and embryo utilisation rates. However, this is not always followed by elevated live birth rates. We argue that this discrepancy relates to failure in addressing other causes of poor-prognosis (from factors herewith described in IVF history) along with the wastage of transferring more than a single embryo in the fresh cycle, when ANZARD data indicates a significantly higher chance of live birth from frozen embryo transfers.